Advancing Digital Literacy and Equitable Learning Outcomes with Local E-Learning Platforms in Primary Schools - Seran, Gregorius; Kurniawan, Yulius (Bulletin of Science, Technology and Society, 2025)
This paper critically investigates how the adoption of local e-learning platforms affects digital literacy advancement and learning outcomes in primary school education. Focusing on disparities in access and the influence of pedagogical and evaluative design, the study employs a qualitative literature review approach with thematic synthesis. Results highlight that, while technology holds promise for leveling educational opportunities, digital equity is contingent upon comprehensive system support extending beyond mere device provision. Responsive instructional design, robust assessment mechanisms, and meaningful collaboration among teachers, families, and community stakeholders are crucial for ensuring that e-learning platforms facilitate not only technical access but also genuine engagement and skill mastery. The investigation reveals that digital literacy for primary students flourishes where digital platforms are integrated into school cultures that value inclusivity, formative feedback, and adaptive learning. The research underscores the need for ongoing structural investments, sustained professional development, and policy frameworks attuned to local heterogeneity. This study offers essential insights for the strategic expansion of digital learning, contributing to a more reflective and equitable digital education ecosystem for young learners.